2020
DOI: 10.1155/2020/8459303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Molecular Pretreated Tumor Profiles as Predictive Biomarkers of Therapeutic Response and Survival Outcomes after Neoadjuvant Therapy for Rectal Cancer in Moroccan Population

Abstract: Pathologic features depending on tumor response to preoperative chemoradiotherapy are important to determine the outcomes in patients with rectal cancer. Evaluating the potential predictive roles of biomarker expression and their prognostic impact is a promising challenge. We reported here the immunohistochemical staining of a panel marker of mismatch repair protein (MMR), Ki67, HER-2, and p53. Additionally, identification of somatic mutations of KRAS, NRAS, and BRAF genes were performed by direct sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Lopez et al found that, although 50% of the patients had mutations in TP53, no correlation between changes of p53 in cancer tissue and different responses to radiotherapy was found [ 74 ]. Another study on the Moroccan population found a high expression of p53 in tumor tissue in 93% (39) of patients with an incomplete response and in only 7% of complete responders, demonstrating that p53 may be of prognostic value in the therapeutic response of LARC [ 75 ]. Similarly, Hur et al found that 46.9% of patients with low-expressed p53 in their tumor tissue achieved pCR, whereas only 24.5% of patients with overexpressed p53 were able to achieve pCR [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lopez et al found that, although 50% of the patients had mutations in TP53, no correlation between changes of p53 in cancer tissue and different responses to radiotherapy was found [ 74 ]. Another study on the Moroccan population found a high expression of p53 in tumor tissue in 93% (39) of patients with an incomplete response and in only 7% of complete responders, demonstrating that p53 may be of prognostic value in the therapeutic response of LARC [ 75 ]. Similarly, Hur et al found that 46.9% of patients with low-expressed p53 in their tumor tissue achieved pCR, whereas only 24.5% of patients with overexpressed p53 were able to achieve pCR [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, no significant association was found between Ki67/proIDX expression with gender, age of the subjects, localization of the tumor in the colon and with the histological grade of colorectal cancer. However, there is an observation in the literature about a significant correlation the high expression of Ki67 with an older age of patients [17].…”
Section: Discussionmentioning
confidence: 98%
“…El Otmani et al 6 found that in rectal cancer patients, KRAS mutations at codon 146 were associated with increased recurrence rates and distant metastases, but there was no significant association with overall survival. In this study, BRAF mutations were absent in pretreated tumour biopsies.…”
Section: Discussionmentioning
confidence: 99%